Gold catalysis in quinoline synthesis - Zhao, Ximei; Wang, Guanghui; Hashmi, A. Stephen K. (Chemical communications, 2024)
Quinolines are biologically and pharmaceutically important N-heterocyclic aromatic compounds, which have broad applications in medicinal chemistry. Thus, their efficient synthesis has attracted extensive attention, and a broad range of synthetic strategies have been established. Of note, gold-catalyzed methodologies for the synthesis of quinolines have greatly advanced this field. Various gold-catalyzed intermolecular annulation reactions, such as annulations of aniline derivatives with carbonyl compounds or alkynes, annulations of anthranils with alkynes, and annulations based on A3-coupling reactions, as well as intramolecular cyclization reactions of azide-tethered alkynes, 1,2-diphenylethynes, and 2-ethynyl N-aryl indoles, have been developed. This review provides an overview of this exciting research area. Typical achievements in reaction methodologies and plausible reaction mechanisms are summarized.
Gesehen am 19.11.2024